Integrating Comic Strips in the Classroom Amid the Pervasion of Technology - Qomariyah, Fitrotul; Rizky Agustina, Febrina (Critical Review of English-Arabic World Journal, 2023)
There have been pervasive uses of technology and social media in the classrooms to improve the way English skills are taught. However, Indonesian students' proficiency in reading comprehension is still considered to be inadequate due to language barriers, the lack of motivation and the lack of visually engaging English texts. Therefore, the current study attempted to bring back a conventional way of teaching reading comprehension by integrating comic strips as an instructional media in the classroom. Employing Kemmis and McTaggart’s Classroom Action Research, it was found that the implementation of comic strips successfully improved the students’ low reading comprehension skill for 22 junior high school students.